PERFORMANCE OF MUSICAL MODES FROM MAQAM SECTORS - Mukhsimjon Mansurovich Muminov (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The article provides recommendations on breathing control, performance technique, visual expression techniques, and practice in developing students’ voices. The processes of performing maqom sections in ensemble and solo performance, ensuring musical harmony, and monitoring performance skills are highlighted; the international significance of maqom art and the role of students in conveying it to the younger generation are emphasized.